Pharyngeal airway dimensional changes after orthodontic treatment with premolar extractions: A systematic review with meta-analysis - Orabi, Noha; Flores-Mir, Carlos; Elshebiny, Tarek; Elkordy, Sherif; Palomo, Juan Martin (American journal of orthodontics and dentofacial orthopedics, 2021)
The objective of this research was to evaluate the effect of orthodontic extraction on the pharyngeal airway volume and Minimum cross-sectional area (MCA) in growing and adult patients. Seven databases, unpublished gray literature, and the references list of the identified articles were electronically searched for relevant studies that met our eligibility criteria. Included studies assessed the effect of dental extraction or sagittal dental movements on pharyngeal airway dimensions. The quality of the included studies was assessed using the methodological index for nonrandomized studies. In addition, a meta-analysis was conducted using the RevMan 5 (Nordic Cochrane Centre, Cochrane Collaboration, Copenhagen, Denmark). In 7 studies, 268 treated patients with a mean age of 19.1 ± 7.6 years and 342 nonextraction control group subjects with a mean age of 19.3 ± 7.2 years were included. Compared with the control group, no statistically significant difference was found in total, nasopharyngeal, glossopharyngeal, oropharyngeal volume, or MCA (P >0.05) in the extraction group except in oropharyngeal volume in which a statistically significant increase in the volume 0.41 cm3 (95% CI, 0.05-0.80; P = 0.03) was detected. The clinical significance of this increase is questionable. Included studies showed a moderate to high risk of bias. There is no strong evidence to support the concept that premolar extractions in bimaxillary protrusion or crowded growing and adult patients reduce either pharyngeal airway volume or MCA. Moreover, as the level of evidence was considered very low for all variables, the magnitude, and direction of the summaries have to be interpreted with caution. Future studies with better quality could significantly affect the direction and strength of the results. Trial registration number: PROSPERO CRD42018089924. •Pharyngeal airway volume is no affected by premolars extraction.•Minimal cross-sectional area is no affected by premolars extraction.•Cone-beam computed tomography is an imaging tool to evaluate the pharyngeal airway volume.•The level of evidence was considered very low for all variables.